KOMUNIKASI WISATA SITU GUNUNG SUSPENSION BRIDGE DALAM MENGELOLA KUNJUNGAN DI MASA PANDEMI COVID-19 - Verina Irvan Saipan; Mariana Rista Ananda Siregar; Roni Jayawinangun (UNIVERSITAS PAKUAN, 2022)
This study aims to determine and describe Situ Gunung Suspension Bridge Tourism Communication Management in Tourism Management During the Covid-19 Pandemic. This research is motivated by the current condition of the Covid-19 pandemic, so how can the tourism sector carry out strategies for tourism management during the pandemic. The method used in this study was a qualitative descriptive approach. Key informants used as many as 1 person and 4 informants. Data collection techniques used are through interviews, observation, and documentation. The results of this study, Communication Management in the Management of Situ Gunung Suspension Bridge Tourism During the Covid-19 Pandemic, namely by carrying out the Planning, Organizing, Actuating, and Controlling processes which have gone quite well in the management travel during the Covid-19 pandemic. In planning, the tourism manager uses his Instagram social media by multiplying video and image content to inform tourism and the preparation of planned programs has been going well, the organization carried out during the Covid-19 pandemic has no reduction of employees, the implementation of maintaining infrastructure in an efficient manner. periodically, and supervision is carried out by means of evaluation as well as several parties involved in the supervision.